2017
DOI: 10.1080/00036846.2017.1366639
|View full text |Cite
|
Sign up to set email alerts
|

Leading indicators of fiscal distress: evidence from extreme bounds analysis

Abstract: Early warning systems (EWS) are widely used for assessing countries' vulnerability to fiscal distress. A fiscal distress episode is identified as a period when government experiences extreme funding difficulties. Most EWS employ a specific set of only fiscal leading indicators predetermined by the researchers, which casts doubt on their robustness. We revisit this issue by using the Extreme Bound Analysis, which allows identifying robust leading indicators of fiscal distress from a large set. A robust leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Hernandez de Cos et al [23] find that fiscal balance over GDP and real GDP growth are important determinants of debt crisis. Bruns and Poghosyan [69] and Cerovic et al [59] find that primary and overall fiscal balance to GDP ratios have a significant impact on debt crisis. Figure 4 presents the actual and fitted values of the models estimated for the EU-15.…”
Section: Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernandez de Cos et al [23] find that fiscal balance over GDP and real GDP growth are important determinants of debt crisis. Bruns and Poghosyan [69] and Cerovic et al [59] find that primary and overall fiscal balance to GDP ratios have a significant impact on debt crisis. Figure 4 presents the actual and fitted values of the models estimated for the EU-15.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Previous studies in the literature have found that increases in short-term debt, total external debt to GDP ratio, current account deficit to GDP ratio, inflation, level of reserves/GDP ratio, political problems, and trade openness increase the probability of debt crisis. They also find that decreases in foreign exchange reserves, real GDP growth, and primary and overall fiscal balance to GDP ratios are important determinants of debt crises [22,23,25,34,58,59,68,69].…”
Section: Estimation Resultsmentioning
confidence: 99%
“…In summary, although the question of endogeneity is important, the interest of this paper is not to treat this question but rather to highlight the variables linked in a robust way to budgetary deficits, starting from a large number of potential determinants already used in previous studies. Basically, studies whose objective is similar to ours and which rely on a large set of potential determinants do not deal with the issue of endogeneity, even though its importance is not overlooked (see among others, Woo, 2003a;Ghosh and Yamarik, 2004;Serra, 2006;Gassebner, Gutmann, and Voigt, 2016;Bruns and Poghosyan, 2018). However, to control endogeneity to a certain extent, we perform panel regressions with 5-year lagged explanatory variables.…”
Section: The Issue Of Endogeneitymentioning
confidence: 99%
“…Therefore, there are identified four types of criteria to capture this phenomenon: (1) debt default or restructuring, (2) sovereign bond yield pressure, (3) large International Monetary Fund-supported programme and (4) excessive inflation. In many cases these episodes coincide with currency and banking crises as well as may have originated outside of the fiscal sector (Bruns & Poghosyan, 2018, pp. 1455-1456.…”
Section: Introductionmentioning
confidence: 99%